Australia [videorecording (DVD)] - Wright, Ian, 1965-; McCormick, Megan. (Megan Leah); Bingham, Estelle (Destination travel guide series., 2004)
Video tour of Australia. See the Outback, Queensland and the Great Barrier Reef, Perth, Adelaide, Melbourne, Sydney, and more.